1996
DOI: 10.1302/0301-620x.78b5.0780740
|View full text |Cite
|
Sign up to set email alerts
|

Refracture of the Forearm in Children

Abstract: In a retrospective study we reviewed 28 refractures of the forearm in children, which occurred at a mean of 14 weeks after conservative treatment of the primary fracture. The cause for the refracture was incomplete healing of a primary greenstick fracture in 21 cases (84%). Twenty-two recurrent fractures were treated conservatively, but two had a second refracture.Fifteen patients were followed for over two years. Definitive angulation of more than 10° caused a deficit of forearm rotation.To prevent refracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 3 publications
1
36
0
1
Order By: Relevance
“…8,9 The purpose of this study was to determine the risk factors for forearm refracture based on initial fracture severity, initial fracture location, residual fracture line visibility, and residual fracture malalignment. The risk factors leading to refracture in these studies included greenstick type fractures, residual fracture angulation, incomplete fracture healing, midshaft location, and a younger age.…”
mentioning
confidence: 99%
“…8,9 The purpose of this study was to determine the risk factors for forearm refracture based on initial fracture severity, initial fracture location, residual fracture line visibility, and residual fracture malalignment. The risk factors leading to refracture in these studies included greenstick type fractures, residual fracture angulation, incomplete fracture healing, midshaft location, and a younger age.…”
mentioning
confidence: 99%
“…Refractures occurred at areas of incomplete bony union within 5 months of the primary fracture. The so-called "greenstick fracture" has been known to be susceptible to refractures 8,10,14. Bony union on the convex side of the fracture that has a loss of cortex continuity is delayed due to the elasticity of the concave side, which maintains continuity of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to adults, there is a relatively low incidence re-fracture in children. Reports from the 1990s suggest only 5% of children who fracture their forearm will re-fracture within 18 months 8,9. Similarly, in a 2006 study, only 1 case of forearm re-fracture was observed at the same site in 125 female children with 58 fractures followed prospectively for 8 years, or a rate of 1.7% 10…”
Section: Introductionmentioning
confidence: 93%